EKONOMI-POLITIK DAN REAKSI KULTURAL POPULISME KANAN-JAUH DI HUNGARIA DAN POLANDIA - Yoga Suharman; Iman Amirullah; Widia Olandari; Devlyn Daevena Az Zahrah (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2023)
The phenomenon of the rise of far-right populism and the strengthening of identity politics in some Europe countries has received considerable academic and practical attention in the last decade. The rise of far-right populists in the electoral political process and the increasing public support in Hungary and Poland marked a new chapter of political contestation in the region. This article aims to examine how economic and cultural factors influence the rise of far-right populism in those countries. This study employs a qualitative approach with literary analysis and web-based research to obtain complex interplay between political-economy, cultural, and populist-far-right identity politics. This paper argues that the complex interplay between economic inequality and the superiority of traditional culture of “the self” are the triggers for the rise of far-right populist identity politics in Hungary and Poland.